One-step green synthesis and characterization of leaf extract-mediated biocompatible silver and gold nanoparticles from Memecylon umbellatum - Arunachalam KD (Dove Medical Press, 2013)
Kantha D Arunachalam, Sathesh Kumar Annamalai, Shanmugasundaram HariCenter for Environmental Nuclear Research, Directorate of Research, SRM University, Chennai, Tamil Nadu, IndiaAbstract: In this experiment, green-synthesized silver and gold nanoparticles were produced rapidly by treating silver and gold ions with an extract of Memecylon umbellatum leaf. The reaction process was simple and easy to handle, and was monitored using ultraviolet-visible spectroscopy. The effect of the phytochemicals present in M. umbellatum, including saponins, phenolic compounds, phytosterols, and quinones, on formation of stable silver and gold nanoparticles was investigated by Fourier-transform infrared spectroscopy. The morphology and crystalline phase of the nanoparticles were determined by transmission electron microscopy and energy-dispersive x-ray spectroscopy. The results indicate that the saponins, phytosterols, and phenolic compounds present in the plant extract play a major role in formation of silver and gold nanoparticles in their respective ions in solution. The characteristics of the nanoparticles formed suggest application of silver and gold nanoparticles as chemical sensors in the future. Given the simple and eco-friendly approach for synthesis, these nanoparticles could easily be commercialized for large-scale production.Keywords: green synthesis, phytochemicals, saponins, nanoparticles, transmission electron microscopy